Graded Hypercapnia-Calibrated BOLD: Beyond the Iso-metabolic Hypercapnic Assumption - Driver, Ian D.; Wise, Richard G.; Murphy, Kevin (Frontiers in Neuroscience, 2017)
Calibrated BOLD is a promising technique that overcomes the sensitivity of conventional fMRI to the cerebrovascular state; measuring either the basal level, or the task-induced response of cerebral metabolic rate of oxygen consumption (CMRO2). The calibrated BOLD method is susceptible to errors in the measurement of the calibration parameter M, the theoretical BOLD signal change that would occur if all deoxygenated hemoglobin were removed. The original and most popular method for measuring M uses hypercapnia (an increase in arterial CO2), making the assumption that it does not affect CMRO2. This assumption has since been challenged and recent studies have used a corrective term, based on literature values of a reduction in basal CMRO2 with hypercapnia. This is not ideal, as this value may vary across subjects and regions of the brain, and will depend on the level of hypercapnia achieved. Here we propose a new approach, using a graded hypercapnia design and the assumption that CMRO2 changes linearly with hypercapnia level, such that we can measure M without assuming prior knowledge of the scale of CMRO2 change. Through use of a graded hypercapnia gas challenge, we are able to remove the bias caused by a reduction in basal CMRO2 during hypercapnia, whilst simultaneously calculating the dose-wise CMRO2 change with hypercapnia. When compared with assuming no change in CMRO2, this approach resulted in significantly lower M values in both visual and motor cortices, arising from significant dose-dependent hypercapnia reductions in basal CMRO2 of 1.5±0.6%/mmHg (visual) and 1.8±0.7%/mmHg (motor), where mmHg is the unit change in end-tidal CO2 level. Variability in the basal CMRO2 response to hypercapnia, due to experimental differences and inter-subject variability, is accounted for in this approach, unlike previous correction approaches, which use literature values. By incorporating measurement of, and correction for, the reduction in basal CMRO2 during hypercapnia in the measurement of M values, application of our approach will correct for an overestimation in both CMRO2 task-response values and absolute CMRO2.